Analisis pengaruh pertumbuhan ekonomi, indeks pembangunan manusia (IPM) dan upah minimum provinsi (UMP) terhadap kemiskinan di Kabupaten Merangin - Nadya Agustin; M Syurya Hidayat; Etik Umiyati (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
This study aims to analyze: 1) The effect of economic growth, HDI, and Provincial minimum wage (PMW) on poverty levels in Merangin Regency. 2) The effect of economic growth, HDI, and PMW on the depth of poverty in Merangin Regency. 3) The effect of economic growth, HDI, and PMW on the severity of poverty in Merangin Regency. The data used are secondary data during the period 2002-2017. Data analysis tool using multiple linear regression method. Based on the results of the analysis, it is known that: 1) Simultaneously, economic growth, HDI, and PMW have a significant effect on the level, depth, and severity of poverty in Merangin Regency. 2) Partially economic growth has a significant effect on the level, depth, and severity of poverty in Merangin Regency, 3) HDI partially has a significant effect on the level, depth, and severity of poverty in Merangin Regency. 4) The PMW partially has a significant effect on the poverty level, but the PMW has no significant effect on the depth and severity of poverty in Merangin Regency. Keywords: Poverty, Economic growth, HDI,Provincial minimum wage(PMW)